2018
DOI: 10.1152/ajpcell.00060.2017
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal cardiomyocyte hypertrophy induced by endothelin-1 is blocked by estradiol acting on GPER

Abstract: Estradiol (E) prevents cardiac hypertrophy, and these protective actions are mediated by estrogen receptor (ER)α and ERβ. The G protein-coupled estrogen receptor (GPER) mediates many estrogenic effects, and its activation in the heart has been observed in ischemia and reperfusion injury or hypertension models; however, the underlying mechanisms need to be fully elucidated. Herein, we investigated whether the protective effect of E against cardiomyocyte hypertrophy induced by endothelin-1 (ET-1) is mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Nevertheless, E 2E ndo (in the Sham rats) showed much potency at minimizing the upregulations of both ANP and BNP during stress, while E 2E xo (in the OVX + E 2 rats) was unable to downregulate the latter substantially. In conformity with our findings, Goncalves et al (2018) and others had early demonstrated that E 2 exerts antihypertrophic effects via GPER ( Goldstein et al, 2004 ). Also, the discrepancies observed between the antihypertrophic effect of E 2E ndo and E 2E xo might have occurred because other ovarian secretions such as vascular endothelial growth factor (VEGF) may complement the efforts of E 2 in preventing maladaptive cardiomyocyte hypertrophy ( Cai et al, 2015 ).…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, E 2E ndo (in the Sham rats) showed much potency at minimizing the upregulations of both ANP and BNP during stress, while E 2E xo (in the OVX + E 2 rats) was unable to downregulate the latter substantially. In conformity with our findings, Goncalves et al (2018) and others had early demonstrated that E 2 exerts antihypertrophic effects via GPER ( Goldstein et al, 2004 ). Also, the discrepancies observed between the antihypertrophic effect of E 2E ndo and E 2E xo might have occurred because other ovarian secretions such as vascular endothelial growth factor (VEGF) may complement the efforts of E 2 in preventing maladaptive cardiomyocyte hypertrophy ( Cai et al, 2015 ).…”
Section: Discussionsupporting
confidence: 94%
“…The H9C2 cardiomyoblast cells were cultured according to the method of 18,32 with modification. Briefly as soon as cells reached 70% confluency they were passaged, counted and 1 × 10 6 cells seeded and grown on glass cover slips in 6 well plates (NEST, Whitehead scientific).…”
Section: Treatment Of Cellsmentioning
confidence: 99%
“…However, estradiol treatment to OVX SD rats eliminates the OVX-induced increase in renal ET A and ET B receptor expression ( Gohar et al, 2016b ), pointing to estrogen as a regulator for renal ET receptor expression. Indeed, evidence suggest a potential crosstalk between GPER1 and ET-1 signaling pathways within the vascular ( Meyer et al, 2012 ), cardiac ( Goncalves et al, 2018 ), and renal systems ( Gohar et al, 2020 ; Gohar and Pollock, 2021 ). Within the renal medulla of the female SD rat, G1-induced natriuresis is blunted by simultaneous ET A and ET B inhibition ( Gohar et al, 2020 ; Gohar and Pollock, 2021 ), which provides supporting evidence that GPER1 is a female-specific pro-natriuretic factor due to its interactions with the renal ET-1 system, yet these signaling interactions are not completely understood.…”
Section: Introductionmentioning
confidence: 99%